2020
DOI: 10.1002/fee.2217
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal insect migrations: massive, influential, and overlooked

Abstract: During seasonal changes around the globe, trillions of insects are on the move. Many insect populations, including butterflies, moths, hoverflies, and dragonflies, make repeated seasonal migrations each year. It is only during the past century that biologists have come to accept the concept of insect migration, and new research using radar, citizen science, and stable isotopes has revealed unexpected insights about this phenomenon. Drawing on these findings, we demonstrate how seasonal insect movements are bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 54 publications
1
112
0
Order By: Relevance
“…Unfortunately, very little is known about the drivers and mechanisms influencing migratory behaviour (e.g. timing) of insects in general (Satterfield et al., 2020), and even less so for autumn migration specifically (Krauel et al., 2015). Increased insect abundance is, however, often linked to higher precipitation levels (Krauel et al., 2018), and migration theory predicts the optimal time for bat migration to be determined by (changes in) insect abundance (Hedenström, 2009; Krauel & McCracken, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, very little is known about the drivers and mechanisms influencing migratory behaviour (e.g. timing) of insects in general (Satterfield et al., 2020), and even less so for autumn migration specifically (Krauel et al., 2015). Increased insect abundance is, however, often linked to higher precipitation levels (Krauel et al., 2018), and migration theory predicts the optimal time for bat migration to be determined by (changes in) insect abundance (Hedenström, 2009; Krauel & McCracken, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All mentioned direction of recent research on insect radar is especially significant in light of concerns regarding the insect abundance decline [ 132 ]. Satterfield et al [ 133 ] suggested further research and policy priorities to investigate and protect insect migrations concerning the mobile insect population decline and behavioral shift. Similar concerns motivated Stepanian et al [ 104 ] for their work on the aquatic insect abundance decline in North America using radar “at scales that have been previously impossible.” Moreover, radar confirmed that the pest migration is under the severe impact of climate change [ 134 ].…”
Section: Insect Radarmentioning
confidence: 99%
“…This seems to support the thesis that the ecological success of migratory insects depends largely on summer reproduction in high-latitude regions [ 49 ]. The significance of long-distance migrations of dragonflies as a part of the global phenomenon of insect mass migrations should be also emphasized, as the importance and scale of this phenomenon remain largely underestimated [ 50 ].…”
Section: Discussionmentioning
confidence: 99%